2022
DOI: 10.1002/mde.3698
|View full text |Cite
|
Sign up to set email alerts
|

Do business strategies vary across firms in the banking industry? New perspectives from the bank size–profitability nexus

Abstract: This study examines the roles of interdependence and policy variations across firms in the causality between bank size and profitability in Nigeria, using secondgeneration estimators and the Dumitrescu-Hurlin panel Granger non-causality test.The findings support different business strategies and policy variances across banks.Causality is found non-existent in the cases of 11 banks. A unidirectional causality from size to profitability is established in two banks while evidence of a unidirectional causality is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…This class of studies sees CEO pay as a bundle of incentive packages to motivate the executives to perform by implementing policy instruments and actions that actualize the goals and interests of shareholders (Pareek et al, 2023 Accounting ratios and stochastic frontier methods are the two major measures of bank performance in the existing literature. The accounting ratios utilize financial ratios such as return on equity (ROE), ROA, net profit margin, and earnings per share to capture bank performance (Akinlo, 2012;Al-Harbi, 2019;Gupta & Mahakud, 2020;Olaniyi et al, 2023;Olaniyi, Olayemi, et al, 2017;Olawale et al, 2017;Sanusi & Zulaikha, 2019). On the other hand, the stochastic frontier methods employ a standardized efficiency score to explain and capture bank performance (Leykun, 2018;Mutarindwa et al, 2021;Ojeyinka & Akinlo, 2021).…”
Section: Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…This class of studies sees CEO pay as a bundle of incentive packages to motivate the executives to perform by implementing policy instruments and actions that actualize the goals and interests of shareholders (Pareek et al, 2023 Accounting ratios and stochastic frontier methods are the two major measures of bank performance in the existing literature. The accounting ratios utilize financial ratios such as return on equity (ROE), ROA, net profit margin, and earnings per share to capture bank performance (Akinlo, 2012;Al-Harbi, 2019;Gupta & Mahakud, 2020;Olaniyi et al, 2023;Olaniyi, Olayemi, et al, 2017;Olawale et al, 2017;Sanusi & Zulaikha, 2019). On the other hand, the stochastic frontier methods employ a standardized efficiency score to explain and capture bank performance (Leykun, 2018;Mutarindwa et al, 2021;Ojeyinka & Akinlo, 2021).…”
Section: Empirical Evidencementioning
confidence: 99%
“…Meanwhile, in the banking industry, the high level of interdependence among banks is deeper than in other industries. The banks' services are intertwined and interwoven, and they must always rely on one another to provide efficient services and deliveries (Olaniyi et al, 2023). Crediting and debiting banks' accounts in various transactions is possible through numerous interbank services and clearinghouses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among different contextual factors, the business strategies of organizations could be one of the main factors that have a significant influence on future investment decisions and financial performance (Ameer & Othman, 2021; Kong et al, 2020; Lin et al, 2021). From a strategic perspective, both differentiators and cost leaders participate and invest in sustainability activities as part of their organizational strategies and try to build a positive image to increase sales and market share (Chen et al, 2018; Jullian & Ofori‐Dankwa, 2013; Olaniyi et al, 2023). However, because of differences in strategic intents, their involvement in sustainability practices could be different (Yamakawa et al, 2011).…”
Section: Theoretical Background Of the Study: Business Strategy Susta...mentioning
confidence: 99%
“…In addition to those contingency factors, organizational strategies, more specifically business strategies, are also found to have significant influences on organizations' engagement in sustainable practices (Chen et al, 2018; Kong et al, 2020; Lin et al, 2021; Romme et al, 1990). While earlier research revealed the influence of business strategies on sustainability practices, the variations and the reasons for variations of sustainability practices and their relationship with slack resources and business strategies are relatively less researched and known to academics, managers, and policymakers (Ameer & Othman, 2021; Jermias, 2008; Kumar et al, 2021; Lueg et al, 2015; Olaniyi et al, 2023). Considering the lack of knowledge in those areas, this study investigates the relationship between organizational slack resources and variations in business strategies and their subsequent influence on different aspects of sustainability practices.…”
Section: Introductionmentioning
confidence: 99%